2018
DOI: 10.4162/nrp.2018.12.5.443
|View full text |Cite
|
Sign up to set email alerts
|

An association of urinary sodium-potassium ratio with insulin resistance among Korean adults

Abstract: BACKGROUND/OBJECTIVESThis study was conducted to investigate the effects of sodium-potassium ratio on insulin resistance and sensitivity in Korean adults.SUBJECTS/METHODSSubjects were 3,722 adults (1,632 men and 2,090 women) aged 40–69 years participating in the Korean genome and epidemiology study_Ansan and Ansung study. Insulin resistance was assessed using homeostasis model assessment of insulin resistance (HoMA-IR) and fasting insulin, and insulin sensitivity was assessed by using the quantitative insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…In rats, a high-salt diet may promote insulin resistance [47]. In humans, insulin resistance was independently and positively associated with a higher sodium intake [48,49]. The results of our cross-sectional study are in agreement with the hypothesis that a higher sodium intake, possibly via an effect on insulin resistance, promotes the development of NAFLD.…”
Section: Discussionsupporting
confidence: 89%
“…In rats, a high-salt diet may promote insulin resistance [47]. In humans, insulin resistance was independently and positively associated with a higher sodium intake [48,49]. The results of our cross-sectional study are in agreement with the hypothesis that a higher sodium intake, possibly via an effect on insulin resistance, promotes the development of NAFLD.…”
Section: Discussionsupporting
confidence: 89%
“…A cohort study of the general Chinese population reported that a higher dietary Na:K ratio was associated with a higher risk of diabetes (11) , which is consistent with the results of our study. The study involving Korean population suggested that a high Na:K ratio is related to high insulin resistance and low insulin sensitivity (39) . A previous study has reported that the association between urinary Na:K ratio and DBP was stronger in a group with a higher homoeostasis model assessment of insulin resistance than with a lower homoeostasis model assessment of insulin resistance (40) .…”
Section: Discussionmentioning
confidence: 99%
“…Higher potassium intake was associated with enhanced bone mineral density, probably by neutralizing acid load and consequently reducing calcium loss from the bone [20,22,23]. Lower potassium intake was associated with lower insulin sensitivity [21,24].…”
Section: Introductionmentioning
confidence: 93%
“…As a result, the World Health Organization recommends an increase in potassium intake from food for reducing blood pressure and the risks of cardiovascular disease and stroke in adults [19]. Dietary potassium intake may also have a beneficial effect on bone health and insulin sensitivity [20,21]. Higher potassium intake was associated with enhanced bone mineral density, probably by neutralizing acid load and consequently reducing calcium loss from the bone [20,22,23].…”
Section: Introductionmentioning
confidence: 99%